Coincident molecular auxeticity and negative order parameter in a liquid crystal elastomer. Issue 1 (December 2018) - Mistry, D.; Connell, S.; Mickthwaite, S.; Morgan, P.; Clamp, J.; Gleeson, H.
Abstract Auxetic materials have negative Poisson's ratios and so expand rather than contract in one or several direction(s) perpendicular to applied extensions. The auxetics community has long sought synthetic molecular auxetics – non-porous, inherently auxetic materials which are simple to fabricate and avoid porosity-related weakening. Here, we report, synthetic molecular auxeticity for a non-porous liquid crystal elastomer. For strains above 0.8 applied perpendicular to the liquid crystal director, the liquid crystal elastomer becomes auxetic with the maximum negative Poisson's ratio measured to date being -0.74 ± 0.03 – larger than most values seen in naturally occurring molecular auxetics. The emergence of auxeticity coincides with the liquid crystal elastomer backbone adopting a negative order parameter, Q B = -0.41 ± 0.01 – further implying negative liquid crystal ordering. The reported behaviours consistently agree with theoretical predictions from Warner and Terentjev liquid crystal elastomer theory. Our results open the door for the design of synthetic molecular auxetics. Auxeticity in synthetic materials is realised by geometrical design of porous structures rather than on a molecular level. Here the authors demonstrate auxeticity in a non-porous liquid crystal elastomer overcoming porosity related weakening of the material and opening a pathway to designed molecular auxetic materials.